2017
DOI: 10.1002/ccr3.925
|View full text |Cite
|
Sign up to set email alerts
|

Isolated intestinal type angioedema due to ACE‐inhibitor therapy

Abstract: Key Clinical MessageA 42‐year‐old woman presents with abdominal pain after taking her first dose of lisinopril. Visceral angioedema was diagnosed based on clinical suspicion and abdominal computed tomography (CT). Awareness of this rare side effect of a common medication is key to avoid delays in diagnosis and unnecessary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Interestingly, this study found some key characteristics of those with ACEi-induced visceral angioedema, namely women were more affected than men (85%), African Americans were more likely to be affected than other races, and lisinopril (56%) was most often the culprit ACEi 5. The average age of individuals affected was 49.5 years 5. Reported symptoms at presentation included abdominal pain in all patients, 77% with emesis and 47% with diarrhoea 5…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Interestingly, this study found some key characteristics of those with ACEi-induced visceral angioedema, namely women were more affected than men (85%), African Americans were more likely to be affected than other races, and lisinopril (56%) was most often the culprit ACEi 5. The average age of individuals affected was 49.5 years 5. Reported symptoms at presentation included abdominal pain in all patients, 77% with emesis and 47% with diarrhoea 5…”
Section: Discussionmentioning
confidence: 74%
“…In a review by Palmquist and Mathews, the authors found 34 individual reports of ACEi-induced visceral angioedema 5. Interestingly, this study found some key characteristics of those with ACEi-induced visceral angioedema, namely women were more affected than men (85%), African Americans were more likely to be affected than other races, and lisinopril (56%) was most often the culprit ACEi 5. The average age of individuals affected was 49.5 years 5.…”
Section: Discussionmentioning
confidence: 78%
“…ACEi-induced angioedema of the small intestine is a rare adverse reaction1; yet, it is important to recognise this side effect as the drug is one of the most commonly prescribed medications in the country. As the symptoms of visceral angioedema may mimic other diseases, it may lead to misdiagnosis or unnecessary work up and procedures.…”
Section: Descriptionmentioning
confidence: 99%
“…Onset of symptoms is usually within days to weeks of initiation of the drug 2. Patients commonly present with abdominal pain, nausea, vomiting and diarrhoea, and it occurs more frequently in females than males 1. CT of the abdomen is known to show segmental oedema of the small bowel, mild dilatation, straightening and ascites among patients with angioedema 3.…”
Section: Descriptionmentioning
confidence: 99%
“…Furthermore, the new drug combination sacubitril/valsartan (McMurray et al ., ) has the potential to induce non‐allergic angio‐oedema (Bas et al ., ) and a life‐threatening case has been reported recently (Raheja et al ., ). Although intestinal manifestations of non‐allergic angio‐oedema caused by ACEi have been described (Palmquist and Mathews, ), almost all cases induced by RAAS blockers are localized to the upper aero‐digestive tract. Such swellings often require emergency treatment, and fatal cases have been reported (Ulmer and Garvey, ; Oike et al ., ; Dean et al ., ; Atalay et al ., ).…”
Section: Introductionmentioning
confidence: 99%